Identifying the Predictors of Short Term Weight Loss Failure after Roux-En-Y Gastric Bypass - Effat Bahadori; Ali Jafarzadeh Esfehani; Leila Sadat Bahrami; Mohammad Reza Shadmand Foumani Moghadam; Ali Jangjoo; Mohsen Nematy; Afshin Roghani; Reza Rezvani (International Journal of Clinical Practice)
Introduction. Gastric bypass surgery is a gold standard therapy for severe obesity. This study aimed to evaluate anthropometric predictors for short-term excess weight loss (EWL) after Roux-en-Y gastric bypass surgery (RYGB) in a sample of severely obese patients. Materials and Methods. This cohort study was conducted on severely obese candidates for RYGB bariatric surgery in Mashhad, Iran. Indirect calorimetry, anthropometric measurements, and body composition data were collected before, one, and six months after RYGB. Results. Fifty-four participants (43, 79.6% women and 11, 20.4% men) with a mean age of 39.63 ± 9.66 years participated in this study. The mean total weight and BMI loss within six months were 32.89 ± 20.22 kg and 12.37 ± 7.34 kg/m2, respectively. The mean reduction in adipose tissue and fat-free mass was 24.49 kg and 7.46 kg, respectively. The mean resting metabolism rate (RMR) reduction at one and six months after RYGB was 260.49 kcal and 396.07 kcal, respectively. There was a significant difference in mean RMR between the baseline and one and six months after RYGB (p<0.001). There was no significant gender difference in mean weight and BMI loss percentage at six months post-RYGB (p>0.05). Baseline skeletal muscle mass (SMM), excess BMI loss (EBMIL) at first month after surgery, and baseline neck circumference (NC) could predict EWL six months after surgery. Conclusion. Reduced RMR shortly after RYGB may be due to FFM reduction. Some anthropometric and their acute changes after RYGB may predict the short-term EWL in RYGB patients.